Pelvic Ultrasound Findings in Women with Obstetric Fistula: A Cross-Sectional Study of Cases and Controls - Jeffrey P. Wilkinson; Angela M. Bengtson; Ennet Chipungu; Rachel J. Pope; Bonus Makanani; Margaret Moyo; Mwawi Mwale; Jennifer H. Tang (Obstetrics and Gynecology International)
Objective. Obstetric fistula (OF) is a morbid condition caused by prolonged obstructed labor. Women with OF experience profound injury and have high rates of infertility and poor obstetric outcomes. We examined endovaginal ultrasound parameters in women with and without OF. Design/Setting/Sample/Methods. This cross-sectional study enrolled women evaluated at the Fistula Care Centre in Lilongwe, Malawi. Eligibility criteria included age 18–45, prior pregnancy, and a uterus on ultrasound. Participants underwent endovaginal ultrasound with measurement of cervical dimensions. Comparisons were done using t-tests and Fisher's exact test. Among women with OF, linear regression was used to assess whether fistula stage was associated with cervical length. Results. We enrolled 98 cases and 12 controls. Women with OF had shorter cervical lengths (18.8 mm versus 27.3 mm, p < 0.01), as well as shorter anterior (7.0 mm versus 9.3 mm, p < 0.01) and posterior (9.5 mm versus 11.0 mm, p < 0.04) cervical stroma, compared to controls. Conclusion. Women with OF have shorter cervical lengths and anterior and posterior cervical stroma, when compared to women without OF. This may offer a partial explanation for subfertility and poor obstetric outcomes in OF patients. Additional studies to clarify the role of ultrasound in OF patients and prediction of future fertility are warranted.